A tutela jurisdicional efetiva nas ações de execução por quantia certa em face da Fazenda Pública - Thomaz, Osvir Guimarães (2010)
The thesis proposes to analyze the effectiveness of civil process regarding the attachment and garnishment actions for debts of the Public Administration. The issue is relevant because the process effectiveness has become the new trend in civil process, and because the Public Administration is the major defendant in all levels of the Judiciary, being the Federal Government, the States, Federal District, Municipalities or Agencies. Therefore it is mandatory to analyze the privileges granted to the Public Administration as instrument for or impediment against the effectiveness of process, as mentioned by the Federal Constitution. One of the Public Administration s privileges the Constitution established is that payments owed by the Federal, State, and Municipal Governments, from any judicial decision are to be made exclusively in the order Judicial Awards for Payment by Public Administration are filed. What is this typical Brazilian institute called Judicial Award for Payment by Public Administration? What is the impact of such institute on process effectiveness? Would such institute be considered constitutional when one interprets systematically the Constitution? Considering the principles of unity of the Constitution and maximum effectiveness, are the Amendments # 30/2000 and 62/2009 that have established an actual moratorium to Public debts already awarded and waiting on the line legally adequate? While the Constitution is facing a big challenge by the proposed Constitutional Amendments from Congress an examination of their unconstitutionality is called for. If such examination is not done provisions from fundamental rights granted by the Constitution may be disregarded. And if there is no profound paradigm break it is possible the process effectiveness against the Public Administration becomes an utopia, and all litigants against the Public Administration remain with the uncomfortable feeling of injustice. In such a case, the Judiciary Power is not going to be able to work as an instrument of social pacification